The Burden of Obesity in Cardiac Surgery: A 14 years’ Follow-Up of 14.754 Patients - Alexander Beckmann; Maximilian Poehlmann; Patrick Mayr; Markus Krane; Johannes Boehm (Journal of Obesity)
Aims. The prevalence of obesity is rapidly increasing during the past decades. While previous research has focused on the early outcome after cardiac surgery or specific complications, the current study covers the whole burden of obesity in the field of cardiac surgery over short term and long term. Endpoints of the study were all-cause mortality, perioperative outcome, and wound-healing disorders (WHDs). Methods. 14.754 consecutive patients who underwent cardiac surgery over a 14 years’ time period were analyzed. BMI classifications were used according to the WHO definition. Results. Mean survival was 11.95 years ± 0.1; CI 95% [12.04–12.14]. After adjustment for clinical baseline characteristics, obesity classes’ I–III (obesity) did not affect 30-day mortality or all-cause mortality during the whole observational period. After adjustment for known risk factors, the risk for WHDs doubled at least in obesity patients as follows: obesity I (OR = 2.06; CI 95% [1.7–2.5]; p<0.0001), obesity II (OR = 2.5; CI 95% [1.83–3.41]; p<0.0001), and obesity III (OR = 4.12; CI 95% [2.52–6.74]; p<0.0001). The same applies to the risk for sternal reconstruction that is substantially elevated in obesity I (OR = 2.23; CI 95% [1.75–2.83]; p<0.0001), obesity II (OR = 2.81; CI 95% [1.91–4.13]; p<0.0001), and obesity III (OR = 2.31; CI 95% [1.08–4.97]; p=0.03). No significant correlation could be found between obesity and major adverse events in the perioperative course like renal failure, ventilation >24 h, re-exploration, or cerebrovascular events. Conclusions. Cardiac surgery is safe in obesity as short- and long-term mortality are not increased, and major adverse events during the perioperative course are similar to control patients. The burden of obesity lies in substantially increased rates of wound-healing disorders and sternal reconstructions.